ANALYZING THE ROLE OF STRATEGIC ALLIANCES IN ENHANCING COMPETITIVE ADVANTAGE IN GLOBAL MARKETS - Fatmasari, Raden (KRIEZ ACADEMY : Journal of development and community service, 2025)
Background: Strategic alliances have become a crucial strategy for organizations seeking to enhance their competitive advantage in global markets. These collaborations allow firms to share resources, expertise, and market access, which can lead to innovation, cost reduction, and market expansion. However, managing these alliances presents challenges, such as cultural differences and misaligned goals. This research explores the role of strategic alliances in enhancing competitive advantage, focusing on the factors contributing to their success and providing insights into best practices for effective alliance management. Aims: This study aims to analyze how strategic alliances contribute to competitive advantage in global markets. Specifically, it seeks to examine the key factors influencing the success of these alliances, including resource sharing, innovation, market access, cultural integration, and sustainability. The research also aims to identify best practices and potential challenges in forming and managing strategic alliances. Research Method: A qualitative case study approach was used, focusing on six strategic alliances across industries such as pharmaceuticals, technology, retail, and automotive. Data were collected from secondary sources, including academic journals, industry reports, and company documents. The research analyzed key themes such as resource sharing, innovation, market access, and cultural integration through thematic analysis to draw conclusions about the success factors of strategic alliances. Results and Conclusion: The study found that strategic alliances are essential for enhancing competitive advantage by facilitating resource sharing, innovation, and market access. Successful alliances are characterized by clear goal alignment, effective communication, and cultural integration. Alliances that prioritize sustainability and risk management tend to have better long-term outcomes. The research concludes that strategic alliances are a powerful tool for gaining a competitive edge in global markets, provided they are managed effectively. Contribution: This research contributes to the understanding of strategic alliances by identifying the factors that drive their success and offering practical insights for firms looking to form or manage alliances. The study highlights the importance of cultural integration, sustainability, and risk management in successful partnerships, providing a framework for future research and practical applications in the field.